2010
DOI: 10.1152/ajpregu.00392.2009
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac and metabolic changes in long-term high fructose-fat fed rats with severe obesity and extensive intramyocardial lipid accumulation

Abstract: Metabolic syndrome and obesity-related diseases are affecting more and more people in the Western world. The basis for an effective treatment of these patients is a better understanding of the underlying pathophysiology. Here, we characterize fructose- and fat-fed rats (FFFRs) as a new animal model of metabolic syndrome. Sprague-Dawley rats were fed a 60 kcal/100 kcal fat diet with 10% fructose in the drinking water. After 6, 12, 18, 24, 36, and 48 wk of feeding, blood pressure, glucose tolerance, plasma insul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
37
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 47 publications
7
37
2
Order By: Relevance
“…Reduced activities of AMPK and PDH have been observed in the myocardium in models of insulin resistance and/or high-fat feeding (1,9,25,51), and reduced activity of either enzyme exacerbates myocardial contractile dysfunction after ischemia and reperfusion (29,44). However, in the present model, we found no evidence that either assigned diet or ischemia-reperfusion influenced the phosphorylation of AMPK, PDH activity, or expression of the major PDH regulatory kinases PDK2 and PDK4 in the myocardium.…”
Section: Discussioncontrasting
confidence: 61%
“…Reduced activities of AMPK and PDH have been observed in the myocardium in models of insulin resistance and/or high-fat feeding (1,9,25,51), and reduced activity of either enzyme exacerbates myocardial contractile dysfunction after ischemia and reperfusion (29,44). However, in the present model, we found no evidence that either assigned diet or ischemia-reperfusion influenced the phosphorylation of AMPK, PDH activity, or expression of the major PDH regulatory kinases PDK2 and PDK4 in the myocardium.…”
Section: Discussioncontrasting
confidence: 61%
“…Additionally, animal studies have observed that fructose intake may play a role in the development of local fat depots. [55][56][57] To date, however, no study in humans has examined the effects of sugar on local ectopic depots, including such sites as the kidney, pancreas, heart, and blood vessels.…”
Section: Discussionmentioning
confidence: 99%
“…LV samples were prepared according to Axelsen et al (24). Protein concentrations were determined by the BCA Protein Assay Kit (Pierce Biotechnology) using BSA as a standard.…”
Section: Methodsmentioning
confidence: 99%